Pengaruh Tekanan Ketaatan, Kompleksitas Tugas, Dan Independensi Terhadap Kualitas Audit Pada Kantor Inspektorat Kota Metro - Rahayu, Sri; Zanaria, Yulita; Hendri, Nedi (Universitas Muhammadiyah Metro, 2023)
This study aims to analyze obedience pressure (1), task complexity (2), independence (3) on audit quality at the metro city inspectorate office. The population in this study were 35 respondents. The sampling technique in this study used the convenience sampling method. This method is where all the population is sampled. This research data uses SPSS for windows software with multiple linear regression analysis testing. The results of this study indicate that the pressure of obedience, task complexity, independence simultaneously affect the quality of audits at the metro city inspectorate office